Master Regulator Activating Transcription Factor 3 (ATF3) in Metabolic Homeostasis and Cancer - Ku, Hui-Chen; Cheng, Ching-Feng (Frontiers in Endocrinology, 2020)
Activating transcription factor 3 (ATF3) is a stress-induced transcription factor that plays vital roles in modulating metabolism, immunity, and oncogenesis. ATF3 acts as a hub of the cellular adaptive-response network. Multiple extracellular signals, such as endoplasmic reticulum (ER) stress, cytokines, chemokines, and LPS, are connected to ATF3 induction. The function of ATF3 as a regulator of metabolism and immunity has recently sparked intense attention. In this review, we describe how ATF3 can act as both a transcriptional activator and a repressor. We then focus on the role of ATF3 and ATF3-regulated signals in modulating metabolism, immunity, and oncogenesis. The roles of ATF3 in glucose metabolism and adipose tissue regulation are also explored. Next, we summarize how ATF3 regulates immunity and maintains normal host defense. In addition, we elaborate on the roles of ATF3 as a regulator of prostate, breast, colon, lung, and liver cancers. Further understanding of how ATF3 regulates signaling pathways involved in glucose metabolism, adipocyte metabolism, immuno-responsiveness, and oncogenesis in various cancers, including prostate, breast, colon, lung, and liver cancers, is then provided. Finally, we demonstrate that ATF3 acts as a master regulator of metabolic homeostasis and, therefore, may be an appealing target for the treatment of metabolic dyshomeostasis, immune disorders, and various cancers.